Connecting with the Viewer: Affectivity and Cathexis in Textile Artwork. (3rd July 2019) - Ayling-Smith, Beverly
Abstract: This article explores how, following bereavement, textile artwork may be able to make a connection with the viewer and allow a progression of their work of mourning. It takes an interdisciplinary approach, drawing from the literature of psychoanalytical theory, affectivity, and textile thinking to understand the importance of cloth as artwork in the grieving process. The article draws on the practice-based textile research of the author which, together with responses to the artworks made, discusses the way viewers can make an emotional investment in textile artwork and considers the concept of exhibitionary affect to increase the emotional connection of the viewer to the work.